Welcome! Check out our free B-School Guides to learn how you compare with other applicants.

This topic has 1 expert reply and 3 member replies
GmatKiss GMAT Titan
Joined
26 Jul 2011
Posted:
2790 messages
Followed by:
41 members
Thanked:
205 times
Target GMAT Score:
700+
GMAT Score:
640
Elapsed Time: 00:00
• Lap #[LAPCOUNT] ([LAPTIME])

Need free GMAT or MBA advice from an expert? Register for Beat The GMAT now and post your question in these forums!
aneesh.kg GMAT Destroyer!
Joined
16 Apr 2012
Posted:
382 messages
Followed by:
24 members
Thanked:
174 times
Sun May 06, 2012 12:30 pm
The expression resembles this form:
(a - b)^2
where
a = (7 + (29)^0.5)^0.5
b = (7 - (29)^0.5)^0.5

(a - b)^2
a^2 + b^2 - 2ab
a^2 = 7 + (29)^0.5
b^2 = 7 - (29)^0.5
2ab = 2*[(7 + (29)^0.5)(7 - (29)^0.5)]^0.5
= 2*[20]^0.5
= 4*[5]^0.5

So (a - b)^2
= 7 + 7 - 4[5]^0.5
= 14 - 4[5]^0.5

_________________
Aneesh Bangia
GMAT Math Coach
aneesh.bangia@gmail.com

Last edited by aneesh.kg on Sun May 06, 2012 12:53 pm; edited 1 time in total

GmatKiss GMAT Titan
Joined
26 Jul 2011
Posted:
2790 messages
Followed by:
41 members
Thanked:
205 times
Target GMAT Score:
700+
GMAT Score:
640
Sun May 06, 2012 12:47 pm
aneesh.kg wrote:
The expression resembles this form:
(a - b)^2
where
a = (7 + (29)^0.5)
b = (7 - (29)^0.5)

(a - b)^2
a^2 + b^2 - 2ab
a^2 = 7 + (29)^0.5
b^2 = 7 - (29)^0.5
2ab = 2*(7 + (29)^0.5)(7 - (29)^0.5)
= 2*(49 - 29) = 40

So (a - b)^2
= 7 + 7 - 40
= - 26

Wrong! You missed the whole root!!!

aneesh.kg GMAT Destroyer!
Joined
16 Apr 2012
Posted:
382 messages
Followed by:
24 members
Thanked:
174 times
Sun May 06, 2012 12:54 pm
Ah, Yes I did. Thanks.
Corrected the post above.

Corrected Solution:

The expression resembles this form:
(a - b)^2
where
a = (7 + (29)^0.5)^0.5
b = (7 - (29)^0.5)^0.5

(a - b)^2
a^2 + b^2 - 2ab
a^2 = 7 + (29)^0.5
b^2 = 7 - (29)^0.5
2ab = 2*[(7 + (29)^0.5)(7 - (29)^0.5)]^0.5
= 2*[20]^0.5
= 4*[5]^0.5

So (a - b)^2
= 7 + 7 - 4[5]^0.5
= 14 - 4[5]^0.5

_________________
Aneesh Bangia
GMAT Math Coach
aneesh.bangia@gmail.com

### GMAT/MBA Expert

GMATGuruNY GMAT Instructor
Joined
25 May 2010
Posted:
6230 messages
Followed by:
1066 members
Thanked:
5438 times
GMAT Score:
790
Sun May 06, 2012 1:39 pm
Quote:
What is the value of [√(7+√29) - √(7-√29)]²?

-26

2√29

14-4√5

14

14+4√5
The square of a value must be nonnegative.
Eliminate A.

Ballpark.
[√(7+√29) - √(7-√29)]²

≈ [√(7+6) - √(7-6)]² Since √25=5 and √36=6, √29 is between 5 and 6.

≈ (√13 - 1)²

≈ 3² Since √9=3 and √16=4, √13 is between 3 and 4.

≈ 9.

Since we overestimated the value of √13-1, the correct answer must be less than 9.

14-4√5 ≈ 14-8 ≈ 6.

If we couldn't ballpark because the answer choices were closer in value, we could use the following approach.

Remembering that (a-b)² = a²-2ab+b², use substitution:
Let x=7 and y=√29.
Substituting x=7 and y=√29 into [√(7+√29) - √(7-√29)]², we get:

(√(x+y) - √(x-y))²

= (x+y) - 2√((x+y)(x-y)) + (x-y)

= 2x - 2√(x²-y²)

= 2*7 - 2√(7² - 29)

= 14 - 2√20

= 14 - 4√5.

_________________
Mitch Hunt
GMAT Private Tutor and Instructor
GMATGuruNY@gmail.com
If you find one of my posts helpful, please take a moment to click on the "Thank" icon.
Contact me about long distance tutoring!

Free GMAT Practice Test How can you improve your test score if you don't know your baseline score? Take a free online practice exam. Get started on achieving your dream score today! Sign up now.

### Best Conversation Starters

1 vipulgoyal 32 topics
2 hemant_rajput 23 topics
3 guerrero 18 topics
4 abhirup1711 17 topics
5 sana.noor 16 topics
See More Top Beat The GMAT Members...

### Most Active Experts

1 Brent@GMATPrepNow

GMAT Prep Now Teacher

211 posts
2 GMATGuruNY

The Princeton Review Teacher

137 posts
3 Jim@StratusPrep

Stratus Prep

60 posts